Validating excised rodent lungs for functional hyperpolarized xenon-129 MRI - Lilburn, David M.L.; Hughes-Riley, Theodore; Six, Joseph S.; Stupic, Karl F.; Shaw, Dominick E.; Pavlovskaya, Galina E.; Meersmann, Thomas (Public Library of Science, 2013)
Ex vivo rodent lung models are explored for physiological measurements of respiratory function with hyperpolarized (hp) 129Xe MRI. It is shown that excised lung models allow for simplification of the technical challenges involved and provide valuable physiological insights that are not feasible using in vivo MRI protocols. A custom designed breathing apparatus enables MR images of gas distribution on increasing ventilation volumes of actively inhaled hp 129Xe. Straightforward hp 129Xe MRI protocols provide residual lung volume (RV) data and permit for spatially resolved tracking of small hp 129Xe probe volumes during the inhalation cycle. Hp 129Xe MRI of lung function in the excised organ demonstrates the persistence of post mortem airway responsiveness to intravenous methacholine challenges. The presented methodology enables physiology of lung function in health and disease without additional regulatory approval requirements and reduces the technical and logistical challenges with hp gas MRI experiments. The post mortem lung functional data can augment histological measurements and should be of interest for drug development studies.